2013
DOI: 10.5851/kosfa.2013.33.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Garcinia cambogia Extract on the Adipogenic Differentiation and Lipotoxicity

Abstract: This study aimed to examine the mechanisms underlying the effects of Garcinia cambogia extract on the adipogenic differentiation of 3T3-L1 cells and long-chain saturated fatty acid-induced lipotoxicity of HepG2 cells. 3T3-L1 preadipocytes, mouse embryonic fibroblast-adipose like cell line, were treated with MDI solution (0.5 mM IBMX, 1 µM dexamethasone, 10 µg/mL insulin) to generate a cellular model of adipocyte differentiation. Using this cellular model, the anti-obesity effect of Garcinia cambogia extract wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
2
3
1
Order By: Relevance
“…Our results showed that (-)-HCA treatment significantly reduced the amount and total area of lipid droplets in cultured primary chicken hepatocytes. These results were consistent with the previous report which showed that Garcinia cambogia extracts significantly suppressed the adipogenic differentiation of pre-adipocytes and intracellular lipid accumulation in the differentiating adipocytes [66]. The previous study reported that the Garcinia cambogia extracts inhibits lipid droplet accumulation in fat cells without affecting adipose conversion in 3T3-L1 cells [67].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that (-)-HCA treatment significantly reduced the amount and total area of lipid droplets in cultured primary chicken hepatocytes. These results were consistent with the previous report which showed that Garcinia cambogia extracts significantly suppressed the adipogenic differentiation of pre-adipocytes and intracellular lipid accumulation in the differentiating adipocytes [66]. The previous study reported that the Garcinia cambogia extracts inhibits lipid droplet accumulation in fat cells without affecting adipose conversion in 3T3-L1 cells [67].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, G. cambogia extract inhibited adipogenic differentiation in 3T3-L1 adipocytes by suppressing the expression of PPARγ and C/EBPα (E. S. Kang, Ham, Hwang, Lee, & Seo, 2013), which is consistent with our results (Figure 1d). However, our study also shows the inhibitory effect of G. cambogia on preadipocyte proliferation and MCE (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 92%
“…In in vitro studies, Garcinia extract (1 mg/mL) treatment inhibited lipid droplet accumulation in 3T3-L1 preadipocytes (90). Similarly, Garcinia extract was found to inhibit cytoplasmic lipid accumulation as well as adipogenic differentiation of preadipocytes (91,92).…”
Section: Garcinia Cambogia (Hydroxycitric Acid) the Effect Of Hydroxymentioning
confidence: 93%